Liver Glucagon Receptors (GluR): Effect of Exercise and Fasting on Binding Characteristics, GluR-mRNA, and GluR Protein Content in Rats - Melançon, A.; Gagnon, V.; Milot, M.; Charest, É.; Foucher, D.; Péronnet, F.; Unson O’Brien, C. G.; Asselin, E.; Lavoie, C. (Hormone and Metabolic Research, 2013)
The purpose of the study was to investigate the effects of acute exercise and fasting on glucagon receptor (GluR) binding characteristics, GluR-mRNA, and protein content in rat liver. Liver homogenates were prepared and plasma membranes were purified by aqueous 2-phase affinity partitioning in rats fed at rest (control) and after 180 min of swimming exercise and 24 h of fasting (7 rats/group). Saturation curve of plasma membranes incubated with [125I]-glucagon showed significant higher GluR density following exercise and fasting than in the control group (8.19±0.29 and 8.01±0.65 vs. 3.09±0.12 pmol/mg of proteins, respectively). When compared to control rats, GluR Kd was also higher following exercise and fasting (0.46±0.05 and 0.56±0.13 vs. 0.33±0.05 nM, respectively; significantly different for fasting only). Expression of GluR-mRNA and protein content were both significantly higher (~100% and ~90%, respectively) following the 24-h fast than in the control rats, but not following exercise. These results, in line with the literature showing an increased sensitivity of the liver to glucagon following exercise and fasting, indicate that an increased density of GluR on plasma membranes can be obtained by 2 complementary mechanisms: externalization of pre-existing GluR from intracellular pools operative in response to the prolonged exercise, and de novo synthesis of GluR operative only in response to fasting. The reduction in plasma insulin concentration and/or depletion of liver glycogen stores, which results from both prolonged exercise and fasting, could be involved in the control of these mechanisms.
Keywords: de novo synthesis; externalization; glycogen; glucagon/insulin ratio; swimming